The Role of International Human Rights Law in Improving the Law of Internal Armed Conflict - Demeke, Seid Mekonnen (Bahir Dar University Journal of Law, 2022)
Sometimes international humanitarian law (IHL) seems incompatible, if notcontrary to internal war because rules designed for international conflict maynot be applied straightforwardly to internal armed conflicts. To rectify thislegal problem, international and regional tribunals have recently decidedvarious cases concerning internal conflicts by applying international humanrights law (IHRL). This implies that we should reconsider the role of humanrights in improving the law of internal armed conflict. In some regions,including much of Europe, routine compliance with IHRL has been achieved.Parallel to this global trend, commentators such as the InternationalCommittee of the Red Cross (ICRC) are strongly advocating that humanrights law have a role in filling gaps in the law concerning internal armedconflict.